1989
DOI: 10.1203/00006450-198910000-00016
|View full text |Cite
|
Sign up to set email alerts
|

Developmental Patterns of Antioxidant Defense Mechanisms in Human Erythrocytes

Abstract: ABSTRACT. To obtain a profile of erythrocyte antioxidant defense potential during late fetal development, we studied selected antioxidant parameters in blood samples from 65 neonates with birth wt between 520 and 4210 g and from 12 healthy adults. Erythrocyte superoxide dismutase activity did not change significantly with maturation and no significant differences were observed among preterm infants grouped in increasing birth wt categories, term neonates, and adults. Erythrocyte catalase and glutathione peroxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
23
0

Year Published

1991
1991
2014
2014

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(26 citation statements)
references
References 19 publications
3
23
0
Order By: Relevance
“…Our results confirm the lower catalase and glutathione peroxidase levels and the higher glutathione reductase and GSH levels in erythrocytes of newborn babies compared with those of adults ( 18,(22)(23)(24). These findings could be due to the raised reticulocyte count typically present in cord blood.…”
Section: Discussionsupporting
confidence: 80%
“…Our results confirm the lower catalase and glutathione peroxidase levels and the higher glutathione reductase and GSH levels in erythrocytes of newborn babies compared with those of adults ( 18,(22)(23)(24). These findings could be due to the raised reticulocyte count typically present in cord blood.…”
Section: Discussionsupporting
confidence: 80%
“…However, these infants received daily from the 4th wk of life 30 mg of elemental iron, more than twice that supplied to the HiFe infants in this study; even so, the reported activities were approximately twice those reported here. Methodologic differences may have contributed to this disparity and to the contrasting results of several crosssectional studies in which ESOD activities fell (31), remained constant (32,33), or rose (34, 35) with increasing postconceptional age. This preliminary report provides the first data on LBWlpreterm infants followed until 20 wk postnatal age, and on such infants who have not received iron supplements.…”
Section: Discussionmentioning
confidence: 99%
“…[1 -3] These changes and processes greatly increase the production of free radicals, which must be controlled by the antioxidant defence system, the maturation of which follows the course of the gestation. [4,5] This oxidative environment, which increases in premature infants from birth before the 37th week of gestation, appears to involve an immaturity in enzymatic and non-enzymatic antioxidant mechanisms. [6 -11] For this reason, some antioxidants, such as a-tocopherol, ascorbic acid and retinol are given to the foetus during the last period of gestation.…”
Section: Introductionmentioning
confidence: 99%